Interplay Between Autophagy and Wnt/β-Catenin Signaling in Cancer: Therapeutic Potential Through Drug Repositioning - Pérez-Plasencia, Carlos; López-Urrutia, Eduardo; García-Castillo, Verónica; Trujano-Camacho, Samuel; López-Camarillo, César; Campos-Parra, Alma D. (Frontiers in Oncology, 2020)
The widespread dysregulation that characterizes cancer cells has been dissected and many regulation pathways common to multiple cancer types have been described in depth. Wnt/β-catenin signaling and autophagy are among these principal pathways, which contribute to tumor growth and resistance to anticancer therapies. Currently, several therapeutic strategies that target either Wnt/β-catenin signaling or autophagy individually, or the interplay between them are in various stages of development. A few of them specifically block elements that participate in both pathways; they are subject to in vitro studies as well as pre-clinical and early clinical trials. Strikingly, drugs designed for other diseases also impact these pathways, which is relevant since they are already FDA-approved and sometimes even routinely used in the clinic. The main focus of this mini-review is to highlight the importance of drug repositioning to target the Wnt/β-catenin signaling and autophagy pathways, with an emphasis on the interplay between them. Nonetheless, we noticed that this field needs worth further examination, so we hope to inspire research to propose clinical trials focused in drug repositioning.